Bronchial Asthma Among Synthetic Fertilizer Factory Workers Exposed to Ammonia - Dwitya Solihati; Muhammad Ilyas (ILUNI MKK FKUI and PRODI MKK FKUI, 2022)
Background: Ammonia is colorless gaseous compound, lucid and irritating material that is water soluble with a distinctly pungent odor. About 80% of the total usage of ammonia is mainly used to produce synthetic fertilizers. One of the health problems caused by ammonia is bronchial asthma. Ammonia can act as sensitizer or irritant asthmagen depend on their properties, which increased complex interaction of inflammation, airway hyperresponsiveness, and airflow obstruction. However, the causal relationship between ammonia and bronchial asthma is still unclear, so it is necessary to look for some evidence regarding this relationship. The search for evidence also included the seven-step assessment of occupational diagnosis of diseases. Therefore, it can assist occupational medicine doctors who treat patients with bronchial asthma and with a history of ammonia exposure. Methods: The literature searching using the electronic database “PubMed”, “Scopus”, and “Cochrane” search engine. Keywords used were worker, ammonia, and bronchial asthma, ventilatory disorder, respiratory disorder. The articles were selected using the defined inclusion and exclusion criteria. The selected articles were then be critically reviewed based on etiological studies from the Oxford Center of Evidence-Based Medicine. Result: From the five literature obtained, there are differences in results. One article stated that ammonia can increase prevalence risk of bronchial asthma, and other four articles found significant associations between ammonia and reduction in the parameters of pulmonary function. Conclusion: There is a relationship between ammonia exposure and the prevalence of bronchial asthma and reduction of pulmonary function in synthetic fertilizer factory worker. But it is uncertain whether the diagnosis is occupational asthma.